2023
DOI: 10.1590/1516-3180.2022.0257.r1.06072022
|View full text |Cite
|
Sign up to set email alerts
|

Four weeks of exercise regimen for sedentary workers with rounded shoulder posture: a randomized controlled study

Abstract: BACKGROUND: Rounded shoulder (RS) posture causes neck and shoulder pathologies. Mechanical correction taping (MCT) is often incorporated into postural corrective therapies; however, its effects on muscle stiffness are unclear. OBJECTIVE: We investigated the effect of MCT with different tape fabrics, along with exercise, on upper trapezius and pectoralis minor muscle stiffness and the posture of sedentary workers. DESIGN AND SETTING: A randomized controlled study was performed at Aydın Adnan Menderes University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A study of subjects with a CVA of less than 44 to 53° with severe FHP and There was no significant improvement in muscle tone in all the groups. CSE and SSE were performed in this study to improve FHP and decrease muscle tone according to previous studies [13,14], and the muscle tone of the upper trapezius was increased in people with FHP. A previous study observed decreased muscle tone, stiffness, and elasticity of the upper trapezius during SSE [28], but there were no significant differences during SSE in the present study.…”
Section: Many Previous Studies Have Compared the Effects Of Sse And M...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of subjects with a CVA of less than 44 to 53° with severe FHP and There was no significant improvement in muscle tone in all the groups. CSE and SSE were performed in this study to improve FHP and decrease muscle tone according to previous studies [13,14], and the muscle tone of the upper trapezius was increased in people with FHP. A previous study observed decreased muscle tone, stiffness, and elasticity of the upper trapezius during SSE [28], but there were no significant differences during SSE in the present study.…”
Section: Many Previous Studies Have Compared the Effects Of Sse And M...mentioning
confidence: 99%
“…In contrast, the upper trapezius muscle, pectoralis major muscle, and levator scapulae muscle develop an imbalance pattern in the body, such as shortening [14]. Therefore, FHP can lead to postural imbalance, resulting in decreased proprioception.…”
Section: ⅰ Introductionmentioning
confidence: 99%